Prediction of Erosion Hazard Level in Tripe Jaya District Using the Universal Soil Loss Equation (USLE) Method - Murdawati; Devika Rahma Damayanti Yusuf; Nurya Ramadhania; Nadya Novi Rahmadana (Departemen Teknik Geomatika ITS, 2026)
The Tripe Jaya Subdistrict in Gayo Lues Regency features a highly vulnerable landscape where steep slopes, intense rainfall, and limited vegetation cover collectively contribute to severe erosion risk. Erosion in this region threatens soil fertility, agricultural productivity, slope stability, transportation infrastructure, and riverbank integrity. This study aims to predict and map erosion hazard levels using the Universal Soil Loss Equation (USLE) integrated with Geographic Information System (GIS) analysis, based on rainfall, soil type, slope, and land cover data. The results classify the study area into five erosion hazard categories: very light (2,909.09 ha), light (20,669.38 ha), moderate (10,880.66 ha), heavy (432.99 ha), and very heavy (6,922.76 ha), with the most critical zones concentrated in steep and intensively utilized areas. These findings emphasize the substantial erosion risk in Tripe Jaya and provide an essential reference for mitigation planning, land-use regulation, and infrastructure protection, particularly for road segments adjacent to riverbanks.